PERAN DAN KONTRIBUSI ADINEGORO PADA JURNALISME DI INDONESIA - Wahyudi Marhaen Pratopo; Lestantya R. Baskoro (Jurnal Komunikasi & Media Digital, 2023)
The development of journalism can be traced from the history of the media industry and journalism practices as well as the thought of its practitioners. This paper wants to explain the role of Adinegoro in Indonesian journalism. The research uses a constructivist paradigm and qualitative methods. The researchers conducted a literature study, observation, and interview to gather data. The research results show that Adinegoro played a significant role in developing the press, journalism, and language in Indonesia through his involvement in several newspapers, news agencies, journalism thought, and the Indonesian Language Congress.